A AUTORIDADE NACIONAL ANTICORRUPÇÃO (ANAC) - Ramajoli, Margherita (Constituição, Economia e Desenvolvimento: Revista Eletrônica da Academia Brasileira de Direito Constitucional, 2020)
This article aims to analyze the National Anti-Corruption Authority (ANAC). In order to carry out this study, the fight against corruption in the Italian system is first approached. Secondly, the research for the understanding of the National Anti-Corruption Authority (ANAC) as an independent authority for analysis of the problematic approached is verticalized. It then addresses ANAC's institutional missions and its wide range of powers. This study is finalized by analyzing ANAC's responsibility.